Franchise in The Perspective of Islamic Contract Law - Arifin, Bustanul (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2024)
Background. The construction of an agreement based on Islamic Law must fulfill the principles of mu’amalah, the pillars (rukun) and conditions for the validity of the agreement, the provisions of the agreement and the prohibition of cooperating in committing a sin, and the ability of the parties to carry out legal acts. The valid condition of an aqad (agreement) is that the purpose of the agreement is fulfilled as the main consequence of an aqad. Aims. This article examines franchise business agreements according to the normative provisions of Islamic Law. Methods. Library research studies emphasize the legal aspects of franchises. Conceptual data are tracked on the internet with the keywords franchise and Islamic perspective and the results are analyzed descriptively. Results. Franchise is a form of cooperation agreement (syirkah) which provides special rights and authorities to the franchisee as the recipient. Franchise is a reciprocal agreement, because the franchisor as the franchiser and the franchisee, both are obliged to fulfill certain achievements. Franchise agreements are permitted according to Islamic Law because they are beneficial and do not contain elements that conflict with the concept and process of syirkah and fulfill the pillars of ijarah: ‘uqud (people who have aqad, namely the franchisor and franchisee), sighat ‘uqud (found during negotiations), ujrah (wages), and benefits (business).